Sikap, Norma Subjektif, Kontrol Perilaku Persepsian, Sifat Machiavellian dan Niat Melakukan Whistleblowing - Puspita Devi, Ni Wayan; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi, 2024)
This research aimed to determine the effect of attitudes, subjective norms, perceived behavioral control, and machiavellian traits on students' intentions to whistleblowing. The sample used 380 students from 4.282 students population of the Faculty of Economics and Business, Udayana University. This research uses primary data derived from the results of questionnaire answers. The method of determining the research sample used proportionate stratified random sampling. The analysis technique used partial least square. The results indicated that attitudes, subjective norms, perceived behavioral control had a positive effect on students' intentions to whistleblowing while machiavellian traits had no effect on students' intentions to whistleblowing. The implication of this research is to provide empirical support that students' intentions to whistleblowing are supported by attitudes, subjective norms, and perceived behavioral control. Keywords: Whistleblowing Intentions; Attitudes; Subjective Norms; Perceived Behavioral Control; Machiavellian Traits